Double Laser for Depth Measurement of Thin Films of Ice - Manuel Domingo Beltrán; Ramón Luna Molina; Miguel Ángel Satorre Aznar; Carmina Santonja Moltó; Carlos Millán Verdú (Sensors, 2015)
The use of thin films is extensive in both science and industry. We have created an experimental system that allows us to measure the thicknesses of thin films (with typical thicknesses of around 1 µm) in real time without the need for any prior knowledge or parameters. Using the proposed system, we can also measure the refractive index of the thin film material exactly under the same experimental conditions. We have also obtained interesting results with regard to structural changes in the solid substance with changing temperature and have observed the corresponding behavior of mixtures of substances.